Six Ways to Improve the Profitability of Lychee in South Florida - Edward Evans; Robert Degner; Kimberly Morgan (EDIS)
While the decision of whether to remain in the lychee business, shift to alternative enterprises, or sell the land to the real estate developers is a personal decision, this document offers some suggestions to growers on how to increase their returns from lychee. Specifically, it discusses six ways to improve the profitability of lychee enterprises, with an emphasis on marketing. This is EDIS document FE497, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL. Published November 2004.